OTOMATISASI KERAN DISPENSER AIR MENGGUNAKAN SENSOR PHOTODIODE DAN ULTRASONIK - , CHRISTINA TIO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
It has been made an automatic faucet for water dispenser. In this system, the faucet will be opened when the ray from the infrared LED to photodiode is blocked by a non-transparent glass. The water will flow in to the glass through the electric faucet and automatically stop when the gap between the water surface, which is detected by the ultrasonic sensor, and the rim of the cup as far as 1 cm. Since this water dispenser used 7 height level of photodiode sensor, when the glassâs height is not match to the height level of photodiodes, the water will not stop at 1 cm gap. Besides, because of rippling water at the filling process, caused the reading process of ultrasonic sensor a little bit inaccurate.